An update on metabolic assessment in patients with urinary lithiasis - Petean Ruiz Amaro, Carmen Regina [UNESP]; Goldberg, Jose [UNESP]; Damasio, Patricia Capuzzo [UNESP]; Leitao, Victor Augusto [UNESP]; Turney, Benjamin; Padovani, Carlos Roberto [UNESP]; Amaro, Joao Luiz [UNESP] (Springer, 2015)
The objective of this study was to evaluate the prevalence of urinary metabolic abnormalities in patients with urolithiasis and their potential risk factors.A total of 905 stone patients were evaluated in a prospective trial from February 2000 to January 2012. Inclusion criteria were as follows: history and/or imaging tests confirming at least 2 separate or concurrent stone episodes; creatinine clearance a parts per thousand yen60 mL/min; and negative proteinuria and urine culture. Metabolic study consisted of two 24-h urine collections separated by a period of 3 months for dosing Ca, P, uric acid, Na, K, Mg, oxalate, and citrate. Serum levels of Ca, P, uric acid, Na, K, Cl, Mg, creatinine, and glucose were assessed. Urinary pH and urinary acidification tests were also performed.A total of 735 patients were included, with a mean age of the 40 +/- A 1.0 year; 96.8 % of patients presented diagnosis of one or more urinary metabolic abnormalities. The most prevalent metabolic abnormalities were hypercalciuria (50.8 %), hypomagnesuria (50.1 %), hypocitraturia (35.4 %), and hyperuricosuria (30.7 %). Body weight was significantly higher in patients with hyperuricosuria (81.20 +/- A 15.67 kg vs. 70.17 +/- A 14.13 kg, respectively, p = 0.001). Urinary sodium was significantly higher in patients with hypercalciuria than without (246.97 +/- A 103.9 mEq/24 h vs. 200.31 +/- A 91.6 mEq/24 h, p = 0.001) and hyperuricosuria compared to without (283.24 +/- A 107.95 mEq/24 h vs. 198.57 +/- A 85.3 mEq/24 h, p = 0.001).Urinary metabolic disturbances were diagnosed in 96.8 % of patients in the study. These results warrant metabolic study and follow-up in patients with recurrent lithiasis in order to decrease recurrence rate through specific treatments, modification in alimentary, and behavioral habits.
Keywords: Urolithiasis; Risk factors; Metabolic disease; Follow-up studies